Functional characterizations of IPS-1 in CIK cells: Potential roles in regulating IFN-I response dependent on IRF7 but not IRF3. Issue 1 (November 2015) - Feng, Xiaoli; Zhang, Yixuan; Yang, Chunrong; Liao, Lanjie; Wang, Yaping; Su, Jianguo
Abstract: IPS-1, as the sole adaptor of RIG-I and MDA5, plays a central role in innate antiviral immunity. In this study, we investigated potential roles of IPS-1 in innate immunity and the domain-requirement of IPS-1 for its signaling in grass carp ( Ctenopharyngodon idella ). Overexpression experiment showed that CiIPS-1 mediated IFN-I signal possibly dependent on CiIRF7 but not CiIRF3. Post GCRV challenge, CiIPS-1 could enhance antiviral immune responses. CARD and TM domains were crucial for antiviral function of CiIPS-1, and TRAF motif played an assistant role. PRO domain seemed as a negative regulator but was pivotal for the initiation of CiIFN-I and CiMx1. Post viral/bacterial PAMPs stimulation, CiIPS-1-mediated signaling was tightly controlled. CARD domain of CiIPS-1 could significantly elicit poly I:C/LPS/PGN-mediated signaling. PRO domain negatively regulated CiIRF7 and CiIFN-I but was indispensable for inductions of CiMx1 and CiIL-1β. TRAF motif and TM domain regulated the signaling presumably in a cooperative fashion. Post poly I:C stimulation, TRAF motif negatively regulated CiIRF7, CiIFN-I and CiIL-1β at a relative early time while TM domain functioned at a relative late time. TRAF motif was indispensable for the production of CiMx1, while TM domain slightly negatively regulated the expression. Post LPS and PGN stimulation, TRAF motif excited an assistant and persistent negative role on CiIFN-I, CiIRF7 and CiIL-1β induction, but was crucial for induction of CiMx1. TM domain slightly negatively regulated LPS- and PGN-triggered signaling. Taken together, CiIPS-1 not only exerted important functions in antiviral immune response but also participated in viral/bacterial PAMPs-triggered immune response which was tightly controlled to prevent harmful effects resulting from excessive activation. This study provided novel insights into the pivotal role of IPS-1 in innate immunity. Highlights: CiIPS-1 restrained CiIRF3 transcription. TM domain was crucial for antiviral function of CiIPS-1, and TRAF motif played an assistant role. TM domain played a suppressive role in poly I:C-, LPS- and PGN-mediated signalings. CARD domain significantly elicited signaling cascade post poly I:C, LPS and PGN stimulation. CARD domain induced significant production of CiIL-1β post GCRV or viral/bacterial PAMPs stimulation.